Fluid Intake and Hydration Status among Sports Science Students at Cenderawasih University - Sinaga, Evi; Putra, Miftah Fariz Prima; Sinaga, Friska Sari Gracia; Hidayat, Rodhi Rusdiyanto; Sinaga, Eva (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
Fluid intake is often neglected which has an impact on student productivity and achievement as well as the vulnerability of sports students to dehydration. The purpose of this study was to determine the fluid intake and hydration status of sports science studentsat Cenderawasih University. This cross-sectional survey with simple random sampling was conducted among 72 sports science students. The data collected were the characteristics of the subjects (age and BMI), fluid intake, hydration status and hydration knowledge. The hydration status was used to measure the urine color chart through the Self-Urine Check (PURI) card. Fluid intake was assessed using the 3x24 hour recall method and the semi-quantitative Food Frequency Form. The subject's hydration knowledge was assessed by using the Hydration Knowledge Scale (HyKS). The results showed that most of sports sciencestudents (69.4%) were well hydrated while respectively 18.1%, 6.9% and 5.6% were dehydrated in the light, moderate and severe categories. Total fluid intake was 2708.99±416.97 which was dominantly obtained from the water consumption. Hence, although most of the students were well hydrated, they were still found to be dehydrated. Correlation tests showed a very strong positive relationship between total fluid intake and hydration status. Further research involving physical activity variable in sports science students with a larger sample and sports nutritional education need to be conducted.